Fitting Regression Models for Sustainable Management of Non-Timber Forest Products in Forests and Private Lands: A Case Study from Mid-Western Region of Nepal - Pandit, Bishnu Hari; Ghimire, Laxman (The Initiation, 2011)
This study examines the constraining factors for sustainable management of Non-Timber Forest Products (NTFPs) in both community and private forests in Dang, Rolpa and Pyuthan Districts of mid-western Nepal. Four CFUGs were selected from each of the study districts, and NTFP inventory was done. A total of 259 households were randomly sampled for household data collection. Two Focus Group Discussions (FGDs) were held in each district and Key Informant survey was done to assess preliminary information and data. Two regression models were fi tted to investigate the causes of sustainable management of NTFPs. The report revealed that Non-Timber Forest Product (NTFP) cultivation initiated by local farmers in the past have indicated that farmers have planted some species of NTFPs (such as Cinnamon tamala, Swertia, Zanthoxylum, Sapindus) in their farmlands and other community forest lands in the study districts. A regression analysis of constraining factors explored in a household survey revealed that cultivation of NTFP species is significantly influenced by household labour force engaged in cultivation in agriculture on marginal lands and their affiliation with community based local institutions (R2 = 56%). While constraining factors for sustainable management of NTFP in government and community forests are distance from home to forest, food production; active labour force, training on forest management, and household labour force involved in agriculture (R2 = 66%). Recommendations are made for sustainable management of NTFPs in forest and private lands. DOI: http://dx.doi.org/10.3126/init.v4i0.5532 The Initiation Vol.4 2011 14-27